Chronic neuropathic pain reduces opioid receptor availability with associated anhedonia in rat. Issue 9 (September 2018) - Thompson, Scott J.; Pitcher, Mark H.; Stone, Laura S.; Tarum, Farid; Niu, Gang; Chen, Xiaoyuan; Kiesewetter, Dale O.; Schweinhardt, Petra; Bushnell, M. Catherine
Abstract : Abstract: The opioid system plays a critical role in both the experience and management of pain. Although acute activation of the opioid system can lead to pain relief, the effects of chronic pain on the opioid system remain opaque. Cross-sectional positron emission tomography (PET) studies show reduced availability of brain opioid receptors in patients with chronic pain but are unable to (1) determine whether these changes are due to the chronic pain itself or due to preexisting or medication-induced differences in the endogenous opioid system, and (2) identify the neurobiological substrate of reduced opioid receptor availability. We investigated these possibilities using a well-controlled longitudinal study design in rat. Using [ 18 F]-FDPN-PET in either sham rats (n = 17) or spared nerve injury rats (n = 17), we confirmed reduced opioid receptor availability in the insula, caudate–putamen, and motor cortex of nerve injured rats 3 months after surgery, indicating that painful neuropathy altered the endogenous opioid system. Immunohistochemistry showed reduced expression of the mu-opioid receptor, MOR1, in the caudate–putamen and insula. Neither the opioid peptide enkephalin nor the neuronal marker NeuN differed between groups. In nerve-injured animals, sucrose preference, a measure of anhedonia/depression-like behavior, positively correlated with PET opioid receptor availability and MOR1-immunoreactivity in the caudate–putamen. These findings provide new evidence that the altered supraspinal opioid receptor availability observed in human patients with chronic pain may be a direct result of chronic pain. Moreover, reduced opioid receptor availability seems to reflect decreased receptor expression, which may contribute to pain-induced depression. Abstract : Supplemental Digital Content is Available in the Text.Chronic pain reduces opioid receptor expression in the rat striatum, where the correlation between receptor expression and anhedonia may represent a molecular substrate for comorbid depression.